EFFECTIVENESS OF INDUSTRIAL RELATIONS DISPUTE NEGOTIATIONS IN THE INTERESTS OF TRADE UNIONS - Raya Gomal Manalu; Muh Amin Saleh; Muhenri Sihotang; Appe Hutauruk (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
This study aims to analyze the effectiveness of negotiations in resolving industrial relations disputes, particularly in relation to the interests of labor unions in defending the rights of their members. The main focus of this study is directed at the bipartite negotiation mechanism as a mandatory stage before taking the litigation route. Inequality of bargaining power and differences in negotiation strategies often become obstacles in reaching a fair agreement. The research method used is normative juridical with a case approach and a conceptual approach. Data were collected through a literature study of primary, secondary, and tertiary legal materials related to Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes and industrial relations theories. The results of the study indicate that the effectiveness of industrial relations negotiations is greatly influenced by organizational strength, legal capacity, and negotiation strategies implemented by labor unions. It appears that the coherence of litigation strategies and evidentiary strength are the main keys in defending workers’ interests at the cassation level. This study concludes that although bipartite negotiations are a deliberative instrument, their success is highly dependent on the independence or autonomy of trade unions in facing employer domination in order to realize legal certainty and protection of workers’ normative rights.